ENDOMETRIAL PATHOLOGICAL CHANGES IN PERIMENOPAUSE AND POSTMENOPAUSE - ASSOCIATION WITH SOME ANAMNESTIC AND ULTRASONOGRAPHIC PARAMETERS - Kocevska, Ana; Zafirov, Dimche; Petrushevska, Gordana; Ismaili, Bashkim; Skeparovska, Kristina; Georgiev, Dimitar; Tahir, Shenol; Plasheski, Tosho (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
Atypical endometrial hyperplasia is preneoplastic condition that precedes endometrioid adenocarcinoma. Postmenopausal women should not have bleeding; the thickness of the endometrium is normally below 5 mm and if it is above, the presence of a polyp, hyperplasia or cancer is suspected. To determine the histopathological changes of the endometrium, the prevalence of functional and organic changes and their association with history of previous childbirths and abortions, presence of bleeding, intensity of bleeding, anteroposterior uterine diameter and endometrial thickness. The study was performed in the Specialized Hospital for Gynecology and Obstetrics "Mother Teresa" - Skopje and involved a total of 120 respondents who underwent fractionated explorative curettage due to a medical indication. They were divided into 2 groups: with functional and organic changes of the endometrium. Ultrasonographic measurement of anteroposterior diameter of uterus and endometrial thickness was performed. The prevalence of functional changes was 30% and of organic changes 70%. The most common histopathological diagnosis was an endometrial polyp (45% of women). The mean value of endometrial thickness was 7.9 mm in the functional changes group and 13.6 mm in the organic changes group; this difference was statistically significant (p <0.0001). Perimenopausal patients had a significantly longer duration of bleeding than those in postmenopause (p = 0.0009). Endometrial adenocarcinoma was present in 3% of perimenopausal and in 5% of postmenopausal patients. Endometrium was significantly thicker in women with organic changes than in those with functional changes. Perimenopausal patients had a significantly longer duration of bleeding, more intensive bleeding, thicker endometrium and greater anteroposterior uterine diameter than those in postmenopause.    Keywords: fractionated explorative curettage, endometrial thickness, uterine bleeding. https://doi.org/10.55302/JMS2251028k